Rehabilitation Center for Drugs Addicts with Biophilic Architectural Approach - Pakpahan, Ruben Alexandre; Aulia , Dwira Nirfalini (Scientica: Jurnal Ilmiah Sains dan Teknologi, 2024)
Drug cases in the city of Medan, North Sumatra are very troubling. Based on the Indonesia Drugs Report 2022, Medan is the number 1 city in terms of disclosure of drug cases with a total of 6,077 cases and North Sumatra is ranked 1st in the number of prisoners and detainees of drug cases throughout Indonesia. It can be seen that drug cases in Medan city are very worrying, the factors that cause this can come from anywhere, both from the environment, and increasingly uncontrolled relationships. Patients of this abuse have the potential to harm themselves and others. Therefore, a place is needed to recover the addiction of drug abuse victims.